2013
DOI: 10.1073/pnas.1308905110
|View full text |Cite
|
Sign up to set email alerts
|

Tuberous sclerosis 1 (Tsc1)-dependent metabolic checkpoint controls development of dendritic cells

Abstract: Coordination of cell metabolism and immune signals is crucial for lymphocyte priming. Emerging evidence also highlights the importance of cell metabolism for the activation of innate immunity upon pathogen challenge, but there is little evidence of how this process contributes to immune cell development. Here we show that differentiation of dendritic cells (DCs) from bone marrow precursors is associated with dynamic regulation of mechanistic target of rapamycin (mTOR) complex 1 (mTORC1) signaling and cell meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 63 publications
8
88
3
Order By: Relevance
“…Consistent with a role for mTORC1 in DCs, rapamycin, an inhibitor of mTOR, has been shown to selectively inhibit aspects of TLR-driven DC activation in GM-DCs and human monocyte-derived DCs, including the expression of IL-6 and IL-10 and possibly TNF (Cao et al, 2008;Boor et al, 2013;Hussaarts et al, 2013), and diminish their immunogenicity (Haidinger et al, 2010). Moreover, deletion of Tsc1, a negative regulator of mTORC1, allows increased basal expression of activation markers (Wang et al, 2013). Nevertheless, in some circumstances, rapamycin may also promote DC immunogenicity by extending cell longevity .…”
Section: Switching To Warburg Metabolism Allows Cellular Activation Amentioning
confidence: 84%
“…Consistent with a role for mTORC1 in DCs, rapamycin, an inhibitor of mTOR, has been shown to selectively inhibit aspects of TLR-driven DC activation in GM-DCs and human monocyte-derived DCs, including the expression of IL-6 and IL-10 and possibly TNF (Cao et al, 2008;Boor et al, 2013;Hussaarts et al, 2013), and diminish their immunogenicity (Haidinger et al, 2010). Moreover, deletion of Tsc1, a negative regulator of mTORC1, allows increased basal expression of activation markers (Wang et al, 2013). Nevertheless, in some circumstances, rapamycin may also promote DC immunogenicity by extending cell longevity .…”
Section: Switching To Warburg Metabolism Allows Cellular Activation Amentioning
confidence: 84%
“…Recent studies indicated that a Tolllike receptor signaling-mediated metabolic reprogramming is required for DC maturation and antigen presentation (57)(58)(59). Moreover, the dysregulated mTORC1 or the adenosine monophosphate (AMP)-activated protein kinase (AMPK) activity results in an impaired DC development and maturation, indicating a metabolic checkpoint sensing amino acids and intracellular ATP during DC development and maturation (58,60). Our current study further implicated a metabolic checkpoint in DCs requiring the interplay of SIRT1 and HIF1α, two metabolic sensors of redox and oxygen states, respectively (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our data indicate that activation of β-catenin in DCs either genetically or induced by tumors inhibits cross-priming by up-regulating IL-10. mTOR, a serine/threonine kinase that exerts its effects through two complexes, mTOR complex 1 (mTORC1) and mTORC2, plays a critical role in DC development and function (36)(37)(38). Rapamycin-sensitive mTORC1 has emerged as a key regulator of IL-10 in DCs (18,19,36).…”
Section: Discussionmentioning
confidence: 99%